A Review paper on different Pose Invariant Face Recognition Techniques using Neural Networks - Verma, Nivedita; Shukla, Sanyam (International Journal of Computer Sciences and Engineering, 2015)
In existing face recognition techniques researchers have encountered major difficulties while dealing with variation of poses, aging, expressions, and variation in illumination. As the rotations of face parts causes major differences in face image and changes in appearance. For that reason extensive efforts have been taken by vision researchers in area of pose-invariant face recognition in last decade and many salient methodologies have been implemented. This paper provides a literature review of the existing robust face recognition methodologies using neural networks for handling pose invariant and above mentioned issues which caused difficulties in face recognition, it also contains detailed description of presented methods. This paper also includes strengths and drawbacks of these face recognition systems, and several promising directions for future research are also considered.